Toward holistic education: Performance-based student affairs management with social and institutional collaboration - Satunggale Kurniawan; Rahman, Muhammad Afifi; Sugiarno, Yuventius; Eby Era Shevilla (Institute for Advanced Science, Social, and Sustainable Future, 2025)
Background: Student management is an important aspect in school management that aims to provide the best educational services to students. In recent decades, research has emphasized the importance of performance-based student management in improving the quality of education. This approach focuses not only on administrative aspects, but also on the development of student character and competence through structured and measurable programs. Methods: This study uses a qualitative approach with a case study. Data were collected through in-depth interviews, direct observation, and document analysis. The focus of the study includes student planning, student admissions, orientation, attendance arrangements, and student discipline. Findings: This study found that student management is carried out in a structured manner through activity planning, performance-based selection systems, new student orientation, attendance monitoring, and character development through extracurricular activities. The entire process is supported by the use of technology to enhance administrative efficiency and parental engagement. Conclusion: The implementation of performance-based student management can improve the quality of education and shape the character of students better. Schools need to strengthen the student selection system with a more comprehensive method and improve student development programs through a personal approach and the use of educational technology. Novelty/Originality of this article: This study offers new insights into the implementation of performance-based student management in Islamic-based high schools, which can be a model for other schools in improving the effectiveness of student management as a whole.